2018
DOI: 10.2147/ppa.s151736
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antihyperglycemic medications and glucagon-like peptide 1-receptor agonists in type 2 diabetes: clinical consequences and strategies for improvement

Abstract: Adherence to antihyperglycemic medications is often suboptimal in patients with type 2 diabetes, and this can contribute to poor glycemic control, increased hospitalization, and the development of diabetic complications. Reported adherence rates to antihyperglycemics vary widely among studies, and this may be related to differences in methodology for measuring adherence, patient populations, and other factors. Poor adherence may occur regardless of the specific regimen used and whether therapy is oral or injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 74 publications
(136 reference statements)
2
52
0
Order By: Relevance
“…6,7 Literature suggests patients are more likely to adhere to injectable medications administered weekly rather than daily. [8][9][10][11] Clinical outcomes of HbA 1c reduction and weight loss seen in the present study were similar or better than those demonstrated in clinical trials that led to the approval of GLP-1 receptor agonists. The LEAD trials for liraglutide found 1.0%-1.5% reductions in HbA 1c and weight loss varied from 0.2-3.2 kg.…”
Section: Discussionsupporting
confidence: 78%
“…6,7 Literature suggests patients are more likely to adhere to injectable medications administered weekly rather than daily. [8][9][10][11] Clinical outcomes of HbA 1c reduction and weight loss seen in the present study were similar or better than those demonstrated in clinical trials that led to the approval of GLP-1 receptor agonists. The LEAD trials for liraglutide found 1.0%-1.5% reductions in HbA 1c and weight loss varied from 0.2-3.2 kg.…”
Section: Discussionsupporting
confidence: 78%
“…Unless otherwise indicated, results presented are for both dosages of dulaglutide and semaglutide. Active comparators were administered at a daily dosage of 1. options, leading to improvements in clinical outcomes [34]. Over a 6-month period in retrospective studies in the realworld setting, treatment adherence was significantly better with once-weekly exenatide ER than with twice-daily exenatide IR [35,36] and/or once-daily liraglutide [35][36][37], and treatment adherence and persistence rates were significantly higher, and discontinuation rates were significantly lower, with once-weekly dulaglutide than with once-daily liraglutide and once-weekly exenatide [38].…”
Section: Effects Of Once-weekly Glp-1ras On Patient-reported Outcomesmentioning
confidence: 99%
“…Although GLP-1RAs have demonstrated effective glycemic control with a low risk of hypoglycemia and a reduction in body weight [3,8], reported adherence and persistence rates with injectable GLP-1RAs are suboptimal [95][96][97]. This has been partly addressed by the advent of once-weekly injectable GLP-1RAs, which are typically associated with improved adherence and persistence compared with once-or twice-daily agents [96,98,99,100]. Nevertheless, in a US claims-based analysis, approximately 40% of patients were not fully adherent to the once-weekly GLP-1RA dulaglutide after 6 months [96], and suboptimal adherence therefore remains a concern with these therapies.…”
Section: Therapeutic Adherence and Persistence With Injectable Glp-1rasmentioning
confidence: 99%